„Chcę nadmienić, że nie byłem uświadomiony i wykonywałem zadanie jako żołnierz Armii Krajowej”. O wymordowaniu ukrywających się pod Racławicami Żydów przez kompanię miechowskiej AK - Grabowski, Jan (Zagłada Żydów. Studia i Materiały, 2010)
In late November 1943, in Rędziny-Borek near Miechów, a group of armed men, barged into the house of a local peasant, and from a hidden chamber dragged out six Jews hiding there. Then, having searched them thoroughly, and having taken away their valuables and cash, the victims were lined up against the wall and – one by one – shot in the back of the head. The crime, however, was not perpetrated by bandits of some unidentified “forest people”, but a carefully planned (and authorized by the District command) military operation of the Miechów Home Army structures.